THE BENEFIT OF VLOGS INTEGRATION AND ITS EFFECTIVENSS IN TEACHING ENGLISH - Hayatun Nufus; Uswatun Hasanah, Annisa Waghfiliyana, Mumun Munjiah, Naf’an Tarihoran (CV. ADIBA AISHA AMIRA, 2024)
The use of video blogs, or vlogs, as a communication tool in the context of English language teaching has attracted significant attention in educational literature. This research aims to investigate the benefits of vlog integration in improving the effectiveness of English teaching and its impact on the learning process. The literature review method is used to explore and analyze various research that has been carried out in this field. The method used is preferred reporting from systematic review and meta-analitic (PRISMA) method. Findings from literature observations show that the use of vlogs in teaching English can provide significant benefits. One of them is increasing student involvement in the learning process, because videos have a strong visual appeal and can motivate students to participate actively. In addition, vlogs also facilitate independent learning, because students can access learning materials anytime and anywhere according to their needs. The effectiveness of vlog in teaching English is also seen in improving students' language skills. Video blogging allows students to practice speaking, listening, and comprehension skills in an authentic and engaging context. In addition, vlogs can also be used to teach cultural content and relevant daily life situations in an English language context, thereby helping students to understand and apply the language in real contexts. However, despite the many benefits of vlogs integration in English language teaching, research also highlights several challenges that need to be overcome. For example, the selection of appropriate content, the quality of video production, and the availability of adequate technological resources can be obstacles in implementing vlogs in learning.